KSPLORASI PERBANDINGAN ASESMEN MANUAL DAN DIGITAL DALAM LITERASI DIGITAL DI SEKOLAH DASAR - Nurul Amadyah; Rukli Rukli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The increasing integration of digital technology in education raises questions about its effectiveness compared to traditional methods, especially in literacy learning at the primary school level. This study aims to evaluate and compare the implementation of manual and digital assessments to understand their impact on students' literacy development. The research was conducted at SDN 131 Bontobana in Bulukumba Regency, involving 20 fifth-grade students. A descriptive qualitative approach with a case study design was used to explore how both assessment types affect student learning. Data collection involved classroom observations, documentation, and analysis of student performance results from both manual assessments (written exercises) and digital assessments (using the Quizizz platform). The findings show that digital assessments tend to increase students’ motivation, engagement, and efficiency due to their interactive nature and instant feedback features. However, manual assessments still hold a significant role in evaluating students' deeper understanding, critical thinking, and written expression skills. The study concludes that integrating both manual and digital assessment methods can provide a more balanced and effective approach to literacy learning in primary schools, particularly in rural areas with diverse access to digital resources.